RNA metabolism and ubiquitin/ubiquitin-like modifications collide - Pelisch, Federico Gaston (2012)
Alternative splicing and post-translational modifications are key events for the generation of proteome diversity in eukaryotes. The study of the molecular mechanisms governing these processes, and every other step of gene expression, has underscored the existing interconnectedness among them. Therefore, molecules that could concertedly regulate different stages from transcription to pre-mRNA processing, translation and even protein activity have called our attention. Serine/arginine-rich proteins, initially identified as splicing regulators, are involved in diverse aspects of gene expression. Although most of the roles exerted by members of this family are related to mRNA biogenesis and metabolism, few recently uncovered ones link these proteins to other regulatory steps along gene expression, particularly the regulation of post-translational modification by conjugation of the small ubiquitin-related modifier. This along with the established link between ubiquitin, transcription and pre-mRNA processing points to a general mechanism of interaction between different cellular machineries, such as ubiquitin/ ubiquitin-like conjugation pathways, transcription apparatus and the spliceosome.